Opiate-Induced Dopamine Release Is Modulated by Severity of Alcohol Dependence: An [18F]Fallypride Positron Emission Tomography Study - Spreckelmeyer, Katja N.; Paulzen, Michael; Raptis, Mardjan; Baltus, Thomas; Schaffrath, Sabrina; Van Waesberghe, Julia; Zalewski, Magdalena M.; Rösch, Frank; Vernaleken, Ingo; Schäfer, Wolfgang M.; Gründer, Gerhard (Biological psychiatry (1969), 2011)
Preclinical data implicate the reinforcing effects of alcohol to be mediated by interaction between the opioid and dopamine systems of the brain. Specifically, alcohol-induced release of β-endorphins stimulates μ-opioid receptors (MORs), which is believed to cause dopamine release in the brain reward system. Individual differences in opioid or dopamine neurotransmission have been suggested to be responsible for enhanced liability to abuse alcohol. In the present study, a single dose of the MOR agonist remifentanil was administered in detoxified alcohol-dependent patients and healthy control subjects to mimic the β-endorphin-releasing properties of ethanol and to assess the effects of direct MOR stimulation on dopamine release in the mesolimbic reward system. Availability of D2/3 receptors was assessed before and after single-dose administration of the MOR agonist remifentanil in 11 detoxified alcohol-dependent patients and 11 healthy control subjects with positron emission tomography with the radiotracer [18F]fallypride. Severity of dependence as assessed with the Alcohol Use Disorders Identification Test was compared with remifentanil-induced percentage change in [18F]fallypride binding (Δ%BPND). The [18F]fallypride binding potentials (BPNDs) were significantly reduced in the ventral striatum, dorsal putamen, and amygdala after remifentanil application in both patients and control subjects. In the patient group, ventral striatum Δ%BPND was correlated with the Alcohol Use Disorders Identification Test score. The data provide evidence for a MOR-mediated interaction between the opioid and the dopamine system, supporting the assumption that one way by which alcohol unfolds its rewarding effects is via a MOR-(γ-aminobutyric acid)-dopamine pathway. No difference in dopamine release was found between patients and control subjects, but evidence for a patient-specific association between sensitivity to MOR stimulation and severity of alcohol dependence was found.